Large mass movements related to deglaciation effects in southern Peru (Cusco) - Claudia, Giráldez (2013)
The Andes of Peru are among the regions most severely affected by glacier and high-mountain hazards over the past 100 years. Large-scale disasters with thousands of people killed are on record, including ice/rock avalanches, debris flows, and glacier lake outburst floods (GLOF's). Effects of climate change such as glacier retreat and formation of glacier lakes have been one of the drivers of hazards in the past. Now, there is an increasing concern about the destabilizing effect that recent and further warming has a on perennially frozen bedrock and on steep glaciers in the steep flanks of high-mountain peaks, with potentially severe consequences to ice/rock avalanches, which may impact existing and new lakes, producing far-reaching outburst floods. Risks are also changing due to the socio-economic development in the Andean region and need to be considered using integrative approaches.